Ferroptosis-related gene signatures in neuroblastoma associated with prognosis - Chen, Yiru; Li, Zihao; Cao, Qingtai; Guan, Haoyu; Mao, Longfei; Zhao, Mingyi (Frontiers in Cell and Developmental Biology, 2022)
Background: Ferroptosis, a form of regulatory cell death, has been linked to the development of various tumors. Peripheral neuroblastoma (NB) is one of the most common extracranial solid tumors in children, and it has been proposed that regulating tumor cell ferroptosis may be a future treatment for NB. However, it is unclear how ferroptosis contributes to NB development. Methods: Expression data were collected from two independent cohorts (GEO and Arrayexpress databases). Univariate Cox analysis, multivariate Cox analysis, and the least absolute shrinkage and selection operator (Lasso) algorithm were applied to create a prognostic signature, whose performance was quantified using the area under the receiver operating characteristic curve (AUC) and Kaplan–Meier curves. A prognostic meta-analysis was used to test the suitability and stability of the FRG signature. Drug sensitivity analyses were performed using the data collected from Cell Miner™. Results:PROM2, AURKA, STEAP3, CD44, ULK2, MAP1LC3A, ATP6V1G2, and STAT3 are among the eight genes in the FRG prognostic signature, all of which were highly expressed in stage 1 NB, except AURKA. Furthermore, the high-risk group, which was stratified by signature, had a lower overall survival rate than the low-risk group. GSEA revealed that high-risk groups have more biological processes related to ferroptosis. Conclusion: Ferroptosis-related genes are expressed differently between stages 1 and 4 NB. The FRG signature successfully stratified NB patients into two risk groups and can accurately predict the overall survival in NB. In addition, we found that the gene AURKA might have the potential to be a prognostic marker in NB.